Development of E-Dictionary Media in Food Science Courses - Lelly Fridiarty; Mawadda Azizah Sari Waruwu; Nadrah Afiati Nasution (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study addresses the need for innovative learning media in higher education to enhance students’ independent learning, particularly in food science courses. The research aims to develop e-dictionary-based learning media using the Borg and Gall development model. Validation of the media was conducted by material and media experts. The results of the needs analysis show that e-dictionary-based media is highly required for food science courses. Expert validation yielded a material validation percentage of 84% (good category) and media validation of 88% (very good category). Limited trials with students resulted in 87% (very good), while field trials achieved 88.25% (very good). These findings indicate that e-dictionary-based media is suitable for use, especially for introducing cooking herbs and spices. Furthermore, the integration of Android technology supports learning innovation and facilitates more interactive, independent student learning.